Insulin-like growth factor 1 (IGF-1)-induced changes in cardiac inducible nitric oxide synthase (iNOS) in obese rats - Zafirovic, Sonja; Obradovic, Milan; Banjac, Katarina; Sudar-Milovanovic, Emina; Pajcin, Anastasija; Radovanovic, Jelena; Isenovic, Esma R (Frontiers in Endocrinology, 2026)
IntroductionThe role of insulin-like growth factor 1 (IGF-1) in preserving cardiovascular (CV) health, a well-established fact, cannot be overstated. IGF-1 affects inducible nitric oxide synthase (iNOS) activity, contributing to metabolic homeostasis by promoting insulin and glucose metabolism. Excessive iNOS production is involved in the occurrence and progression of insulin resistance and CV diseases (CVD). This study aimed to assess the in vivo impact of IGF-1 on the activity and gene expression of iNOS in the hearts of obese rats, through the extracellular signal-regulated kinase 1/2 (ERK1/2) signaling pathway.MethodsMale adult Wistar rats were fed a standard (Control) or a high-fat (HF) diet for 12 weeks. After the 12th week, half of the Control and HF rats received a single dose of IGF-1 (50 μg/kg, i.p.), while the other half was placebo-treated, and after 24 h the animals were euthanized.ResultsThe in vivo administration of IGF-1 led to a significant increase in nitric oxide (NO), iNOS gene and protein expression, endothelial nitric oxide synthase (eNOS) gene, ERK1/2, and nuclear factor kappa B (NFkB) levels in Control rats. In contrast, HF rats showed a decrease in NO, iNOS protein, and gene, eNOS gene, endothelin-1 and NFkB levels after IGF-1 treatment. Notably, the level of ERK1/2 in HF rats increased following IGF-1 treatment. These results underscore the significant impact of IGF-1 on iNOS activity in obese rat hearts.DiscussionOur findings suggest that the treatment of obese rats with IGF-1 could have significant implications for cardiac function, particularly in the context of obesity, by regulating cardiac iNOS.